Analisis Dampak Perilaku Bulliying Terhadap Prestasi Belajar Siswa - Nursalsabila Muhazzab; Bakri Hasanuddin; Muh. Riswandi Palawa (STIKes Ibnu Sina Ajibarang, 2024)
This research aims to: 1) determine the effect of bullying behavior on student learning achievement; 2) Analyze the impact of bullying behavior apart from its impact on learning achievement. This type of research includes ex post facto research which is carried out on the basis of events or phenomena that occur to find bullying behavior on student learning achievement. The approach taken is a descriptive quantitative approach and a literature review method. This method is used to collect, identify, evaluate and interpret articles that focus on describing the impact of bullying behavior in elementary schools. The research results show that bullying behavior has an impact on students' learning achievement. shows that 15.4% of students' learning achievement in elementary schools is influenced by bullying behavior and the remaining 84.6% is influenced by other causes. Through the literature review method, it was found that bullying behavior can have an impact on poor socialization, low self-confidence, decreased self-esteem in the future, low social skills of students, inability to communicate with other people, experiencing depression, anxiety, and the possibility of hurting themselves.